Outcome after early mobilization following hip reconstruction in children with developmental hip dysplasia and luxation - Gather, Katharina Susanne; Stillfried, Eva von; Hagmann, Sébastien; Dreher, Thomas (World journal of pediatrics, 2018)
BackgroundMost orthopedic surgeons prefer spica cast immobilization in children for 4 to 12 weeks after surgical hip reconstruction in children with developmental hip dysplasia. This challenging treatment may be associated with complications. Studies are lacking that focus on early mobilization without casting for postoperative care after hip reconstruction.MethodsTwenty-seven children (3.4±2.0 years), including 33 hips with developmental hip dysplasia (DDH) and dislocation of the hip (Tönnis grade 1 to 4), who underwent hip reconstruction (Dega acetabuloplasty, varisation-derotation osteotomy and facultative open reduction) were retrospectively included in this study. Postoperatively the patients were placed in an individual foam shell with 30 degrees of hip abduction, hip extension, and neutral rotation. Early mobilization physiotherapy was performed within the first few days after the surgery under epidural anaesthesia. Full weight bearing was allowed after 3-4 weeks. All children received a clinical examination and radiographic evaluation before and after surgical intervention. The follow-up period was 12.3±2.9 months.ResultsOn average, the postoperative acetabular index decreased significantly from 36.9 to 21.7 degrees and the center-edge angle increased from 9.9 to 28.6 degrees. All hips had reached Tönnis grade 1 at the time of the last follow-up. No complications such as dislocation of the bone wedge, avascular necrosis of the acetabulum or femur, lack of non-union, or nerve injury, were reported.ConclusionsIn this cohort study, hip reconstruction was successful according to clinical and radiographic outcome parameters after early mobilization without cast therapy. Early mobilization may be used as an alternative treatment option after hip reconstruction in DDH.
Gesehen am 16.08.2019